Cloning, Expression, Purification and Biological Activities of Recombinant Mouse Interleukin-2 in E. coli M15 - Sanchai Chantajorn; Ratchanee Hongprayoon; Thaweesak Songserm (Agriculture and Natural Resources, 2007)
Molecular cloning, sequencing and expression of recombinant mouse interleukin 2 (rmIL-2) were described. The interleukin-2 (IL-2) cDNA, 450 base pairs in length with repeating CAG, was amplified using specific primers. The IL-2 cDNA showed high homology at 100%, 100%, 91%, 96% and 94% with five strains of mice previously reported (GeneBank accession number AY147902.1, MMU41494, MMU41504, MMU41505 and MMU41506). The IL-2 gene was cloned into the pDrive cloning vector and consequently expressed using pQE30 expression vector which provided high expression level of the recombinant protein. The predicted rmIL-2 sequence is 161 amino acids with a molecular weight of 19 kDa. The expressed protein was then purified by Ni-NTA column under denaturing condition. Analysis of the rmIL-2 by SDS-PAGE demonstrated two bands of 19 and 38 kDa representing monomeric and dimeric forms of this protein. The biological activity in stimulating T-cell proliferation was also described and the binding signal to the receptor was easily observed by immunofluorescence.